Harnessing Artificial Intelligence for Inclusive Education: A Study of Trends, Technologies, and Challenges - Sholikhan, Muhammad; Silalahi, Fujiama Diapoldo (Journal of Education and Teacher Development, 2025)
This study investigates the utilization of Artificial Intelligence (AI) in fostering inclusive education for students with disabilities. Drawing on current literature and visualized trends from 2018 to 2024, this research outlines the rapid growth of AI-related publications addressing inclusive pedagogy. The study maps the key technological applications—ranging from assistive tools and adaptive learning systems to virtual tutoring platforms—and identifies their pedagogical functions in supporting diverse learner needs. It further examines the ethical, infrastructural, and pedagogical challenges encountered in implementation, such as algorithmic bias, limited teacher training, and digital inequality. The findings reveal that AI can significantly enhance accessibility and autonomy for students with disabilities when applied through empathetic, well-regulated, and collaborative frameworks. This paper recommends the development of inclusive and participatory AI design, investment in teacher capacity building, and stronger policy infrastructure to ensure equitable access to AI-powered learning environments. Future directions highlight the importance of ethical considerations and the active involvement of marginalized communities in shaping inclusive digital ecosystems.